2019
DOI: 10.15171/jarcm.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suicidal ideations based on socioeconomic status and mental health among University of Tabriz students

Abstract: Introduction: The purpose of this study was to investigate the association of socioeconomic status and dimensions of mental health with suicidal tendency among students of the University of Tabriz, Iran. Methods: The present descriptive and correlational study was conducted on 900 students of the University of Tabriz in the academic year of 2016-2017. The study tools included the Beck Scale for Suicidal Ideation (BSSI), Symptom Checklist-90-Revised (SCL-90-R), and Socio-Economic Status Questionnaire (SESQ) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…10 Considering that psychotherapy based on self-recognition sources has had a significant effect on variables such as self-esteem, marital satisfaction, positive attitude to addiction, 8 that is, due to the problems associated with addiction including depression, anxiety, amnesia, psychosis, and brain disorders, and social problems such as theft, prostitution, and violence, increased false occupations and reduced efficiency, and a large number of disturbed families, and also according to the number of addicts based on drug addiction statistics in recent years (near to 1.8 to 3.3 million), this area needs to be considered seriously. 11 In this regard, the results of Amirjan et al 12 also showed that psychotherapy based on self-knowledge sources was effective in increasing the selfesteem of high school girls. Girls who took advantage of this therapeutic approach increased their self-esteem by balancing their mental energy and self-decreasing selfesteem.…”
Section: Citation: Mansoori S Mohagheghimentioning
confidence: 96%
“…10 Considering that psychotherapy based on self-recognition sources has had a significant effect on variables such as self-esteem, marital satisfaction, positive attitude to addiction, 8 that is, due to the problems associated with addiction including depression, anxiety, amnesia, psychosis, and brain disorders, and social problems such as theft, prostitution, and violence, increased false occupations and reduced efficiency, and a large number of disturbed families, and also according to the number of addicts based on drug addiction statistics in recent years (near to 1.8 to 3.3 million), this area needs to be considered seriously. 11 In this regard, the results of Amirjan et al 12 also showed that psychotherapy based on self-knowledge sources was effective in increasing the selfesteem of high school girls. Girls who took advantage of this therapeutic approach increased their self-esteem by balancing their mental energy and self-decreasing selfesteem.…”
Section: Citation: Mansoori S Mohagheghimentioning
confidence: 96%